XRF measurements of Amsoldingersee sediment core, Switzerland - Stan Jonah Schouten; Petra Zahajská; Noé Schmidhauser; Andrea Lami; Jacqueline F N van Leeuwen; Petra Boltshauser-Kaltenrieder; Hendrik Vogel; Martin Grosjean (PANGAEA, 2025)
This table contains all high-resolution XRF data accompanying Schouten et al., 2025 in prep. All analytical data were attained from a sediment core taken in Amsoldingersee (46°43 extquotesingleN; 07°34 extquotesingleE; 641 m.a.s.l.); endorheic, small (38 ha; 13 m deep) lake in the Aare valley, located in the Swiss Plateau. The data was collected to get a comprehensive understanding of the interaction between, algal communities, anoxia, temperature and total trophic productivity in the timeframe 11 ka BP - 17 ka BP. Data were attained between January-August 2023. Sediments were collected using a piston corer in 3m segments (UWITEC - style). The sediment cores were cut in 1m pieces before handling. The age-depth relationship is established with a Bayesian model blending 9 14C dates, 3 biostratigraphical markers, and the Laacher see ash layer. XRF data were collected from ITRAX at the University of Bern (0.5 cm resolution, 30 seconds integration time, Cr X-ray tube at 30 kV and 50 mA), centred and log-transformed (CLR).